THE EFFECTS OF THE AUTHORITARIAN PARENTING TOWARD STRESS AND SELF-ESTEEM OF TEENS - Dwi Rahmah Fitriani (Jurnal Ilmu Kesehatan, 2019)
Adolescence is a period of development and a period of adjustment for adult life and a period of stress and stress is a time of turmoil and pressure. At this time, there was a shift in the role of peers who began to "shift" the role of parents. Parents have an impact on adolescent development through the application of authoritarian parenting that is rigid and strict when interacting with adolescents and not infrequently can create tension in the relation of adolescents with parents so that it can provide psychological effects indirectly. Purpose of the study: This study aimed to determine the relation of authoritarian parenting parents with stress levels and adolescent self-esteem. Research methods:: The method used in this study is a correlation with independent variables parenting and self-dependent variable in adolescents. The population in this study were adolescents in vocational high school as many as 218 respondents with a total sample of 141 respondents taken by stratified random sampling technique. The instrument in this study used the Depression Anxiety Stress Scale questionnaire and Rosenberg Self Esteem and for authoritarian parenting, the writer modified the questionnaire then validity test was conducted. The data was then analyzed using the Spearman correlation test. Results: Showing that authoritarian parenting parents with stress levels have a relation with the results of the spearman correlation test rs = 0.002 and for authoritarian parenting parents and self-esteem there is no relation with the results of the Spearman rho correlation test = 0.139. Conclusion: There is a correlation between the authoritarian parenting style of parents and stress levels can be interpreted that parents who apply the type of authoritarian parenting to their teenagers tend to experience stress from mild to severe. There is no relation between parental parenting and adolescent self-esteem. Can be interpreted that the application of authoritarian parenting from parents in adolescents is not related to adolescent self-esteem. Suggestion: Provide positive support to adolescents to prevent adolescents from experiencing stress, and not limit every activity that teens like so that teens can socialize with their environment.